Contested spaces: citizenship and belonging in contemporary times - Meenakshi Thapan (ed.) (New Delhi : Orient BlackSwan, 2010)
Papers presented at a workshop held at Dept. of Sociology, University of Delhi in March 2006.
Keywords: National Characteristics; Ethnopsychology; Cultural Ethnology; Gender Identity